Investigating the Role of Health Promotion Strategies on Lifestyle and Behavioral Changes to Reduce the Number of Non-communicable Disease Patient - Rahman, Rafia (Issues and Development in Health Research Vol. 4, 2021)
Health care services are not only service delivery at the hospital from outdoor, indoor and consultation but also providing health promotional services. Health promotional services have very important role to grow awareness, improve knowledge on practices regarding health. This assist mass population to change knowledge, attitude and practice on different health issues. The sustainable financial independence changes the test and demand for a living. This change plays an important role in changes the lifestyle and behavior pattern of human being. The three most important factors for human lives are work, family and friend, and health. Occupation (work) gives people’s individual identity and recognition in society and world. Successful accomplishment of each task gives people’s confidence and strength. People’s gets peace from family and friends. These two issues are also responsible for social pathology. It leads to deteriorating mental stability and people’s suffering from stress, tension, depression, and anxiety. Lastly, the health by nature people invest on health getting everyday food and people didn’t give concern on health during the healthy time or up to middle age or till fall complete sickness. Present world people were suffering from non-communicable diseases. The causes of this diseases mostly due to the important three issues of human life. Altering of the physiological function of the human body due to the practice of unhealthy lifestyle and social pathology. This paper discusses the connection of lifestyle and behavior with the onset of non-communicable diseases. It will also present the preventive measures for these unhealthy practices and its role to prevent onset, delayed onset of consequences of diseases.